PENGARUH GAME ONLINE DAN EFIKASI DIRI TERHADAP MOTIVASI BELAJAR: (Survey Pada Mahasiswa Jurusan Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan Universitas Siliwangi Tahun Ajaran 2023/2024) - Galih Ahmad Hudaya; Yoni Hermawan; Ai Nursolihat (JOURNAL SAINS STUDENT RESEARCH, 2024)
The research aims to determine the influence of online games and self-efficacy on learning motivation. The research method uses quantitative with an explanatory survey design. The population used was students from the Department of Economic Education, Faculty of Teacher Training and Education, Siliwangi University. The sampling technique used was non-probability sampling, purposive sampling technique, by providing criteria, namely liking or having played online games, so that the total sample taken was 147 people. Data collection techniques in this research used questionnaires, statistical tests used multiple linear regression and coefficient of determination, and the hypothesis tests used were partial tests (t tests) and simultaneous tests (f tests). The research results show that online games and self-efficacy have a partial or simultaneous effect on student learning